Fostering an enabling environment for equality and empowerment in agri-food systems: An assessment at multiple scales - Lecoutere, Els; Achandi, Esther L.; Ampaire, Edidah L.; Fischer, Gundula; Gumucio, Tatiana; Najjar, Dina; Singaraju, Niyati (Elsevier, 2024)
Inequalities by gender and intersecting sources of social differentiation in access to resources, exercise of agency, and desirable outcomes persist in agri-food systems in low- and middle-income countries. Despite decades of development and theoretical assessment efforts calling for multiscale approaches to addressing inequalities in agri-food systems, common approaches remain specific to a scale rather than holistic. In this paper, we make the case that achieving lasting equality and empowerment in agri-food systems requires transformative change. This depends on fostering an enabling environment by relaxing ‘deeper’ – often inter-related – institutionalized constraints to equality and empowerment across multiple nested scales of the state, markets, communities, household, and individuals. Based on a review of recent literature focused on agri-food systems in low- and middle-income countries, we present newly emerging thinking and a status update of key structural constraints to equality at different scales – rooted in policy and discriminatory, formal and informal, social and economic institutions, including norms. We give examples that show how structural constraints to equality at different nested scales are interdependent and mutually reinforcing; demonstrating the need for holistic approaches tackling constraints at multiple scales to foster transformative change in agri-food systems. We recommend designing holistic policy and development programs that combine strategies for relaxing constraints to equality and empowerment at multiple scales using inclusive processes of tailoring and prioritizing. To inform the design of such programs, we present recent evidence of effective or promising strategies for addressing structural constraints to equality that relate to policy, market systems, collectives, and norms.